Feeding problems in infancy and early childhood: Identification and management - Arts-Rodas, Debby (Pulsus Group Inc, 1998)
The purpose of this paper is to present a structured method to assess and manage feeding problems in children under three years of age and a newly developed instrument to assist in the assessment and monitoring of these feeding problems. Simple management strategies and practical suggestions are described, derived from clinical experience and a pertinent review of the literature. Because feeding problems are so prevalent (affecting up to 35% of infants), the use of structured parent questionnaires, interviews and observation scales is important when assessing and managing these problems.